Pig Kahuna : who's that pig? - Sattler, Jennifer Gordon (Bloomsbury, 2015)
At the beach pig brothers Fergus and Dink meet Tallulah, who can whistle, make sand angels, and stand on her head, but while Dink quickly becomes friends with the new pig, Fergus feels a little shy.